Development Model of Family Empowerment and Peer Group Support in Independence of Caring on Indonesian’s Migrant Worker (TKI) Infected by HIV - Nursalam Nursalam; Ah. Yusuf; Ika Yuni Widyawati; Candra Panji Asmoro (Universitas Airlangga, 2015)
Introduction: Human Immunodeficiency Virus (HIV) is a retrovirus that infects cells of the immune system, destroying or damaging the function of cells of the immune system. This makes the immune system becomes weaker, and people become more liable to infection. A lot of new detected HIV transmission source comes from former workers who work abroad. The challenge in dealing the number of transmission performed comprehensive care of patients and their family empowerment and peer support groups. The aimed of this study was to develop the ability of a family of Indonesian Workers who are infected with HIV and Peer Support Group in independence of care.Methods: This study was used an explanatory design and quasy-experimental. Population in this study were the closest family who care for patients infected with HIV during work abroad as migrant workers in East Java. Samples were selected using simple random sampling technique. The independent variable was the peer group and family support, the dependent variable is the level of independence of care on the respondent. Data were collected using a questionnaire that has been tested for validity and reliability and results were tested using the Wilcoxon Signed Rank Test with alpha ≤0.05. Results: The results showed that this method can improve the independence of the family of the HIV-infected client care during labor as migrant workers abroad with a significance value of p=0.004.Conclusion: Empowerment of family and peer group support can be used to increase the independence of families and patients in the treatment of HIV-infected patients during work abroad as migrant workers. Future studies are expected to use a larger sample.